Comparative Effects of Soil and Foliar Applications of Tithonia-Enriched Liquid Organic Fertilizer on Yields of Sweet Corn in Closed Agriculture Production System - Fahrurrozi, Fahrurrozi; Muktamar, Zainal; Setyowati, Nanik; Sudjatmiko, Sigit; Chozin, Mohammad (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2019)
Solid organic fertilizer is commonly applied for organic vegetable production in a closed agriculture production system as nutrient source. However, its availability is considered slow to sweet corn, and thus it is important to make additional nutrients supply as liquid organic fertilizer (LOF) through leaves. The experiments were conducted to compare effects of LOF application methods and to determine optimum LOF concentrations for sweet corn. Two separated factorial experiments, arranged in randomized complete block design with three replicates, were conducted from February to May and March to June 2015, respectively. The first factor was LOF application methods (soil and foliar) and the second factor was LOF concentration (0, 25, 50, 75, and 100 ppm). The observations focused on average weight of husked ear, length, weight and diameter un-husked ears. The results indicated that the effectiveness of soil application of LOF was 99.625 % as effective as foliar application in influencing sweet corn yields. Concentrations of LOF did not increase all observed variables, but yield attributes were within the range of variety description. It is concluded that in a closed production system, LOF application through soil is as effective as foliar application in affecting sweet corn yields.